Canada's New Deal in the Needle Trades - Steedman, Mercedes (Relations industrielles / Industrial Relations, 1998)
The drafting of Canada's industrial standards legislation and its consequences in the clothing industry are examined. In particular, it is argued that the legislation formalized the subordination of specific sectors of workers in the clothing shops. Although the traditional unions made some efforts to organize women, the presence of women in the union bureaucracy was limited. Because of this, the move away from shop-floor unionism towards industry-wide collective bargaining ensured that women had, at best, a peripheral position in union decision making. When the men in the industry sat down to negotiate the legal framework for their trade, most of the political maneuvering went on in a domain exclusive of women. In the negotiations for the legislation in Ontario and Quebec's clothing industry, men reaffirmed the gendered nature of the work in the trade through legal language enshrined in the industrial standards schedules set for the industry.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Clothing industry; Female employees; History; Industrial policy; Labor Unions; Labor relations; Laws & regulations; Legislation; Sex discrimination; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z